IDE BERPOLITIK DENGAN PENDEKATAN NATURAL SEMANTIC METALANGUAGE (NSM) - Manubulu, Isakh Benyamin; Kana, Cynthia Saraswati; Agustina, Santi (Jurnal Nawala Politika, 2024)
Political parties hold significant influence over political ideas in Indonesia. This raises questions about the quality and type of democracy that is aimed for in a party system. By utilizing the NSM approach, it is hoped that it can provide clarity on the fundamental meanings of a political idea in a democratic country. The preparation of this journal was conducted using normative legal research methods with a regulatory-legislation analysis and conceptual approach, as well as a natural semantic metalanguage (NSM) approach. Upon the completion of writing this journal, it was discovered that political ideas using the NSM approach could be explained in various forms such as interests, benefits, inheritance, influence, position, and power. Keywords: Political Ideas, NSM, Political Parties